Non-medical practitioners in the staffing of emergency departments and urgent treatment centres in England: a mixed qualitative methods study of policy implementation - Vari M. Drennan; Mary Halter; Francesca Taylor; Jonathan Gabe; Heather Jarman (BMC, 2023)
Abstract Background Patient demand, internationally, on emergency departments and urgent care treatment centres has grown. Shortages of staff, particularly of emergency medicine doctors, have compounded problems. Some countries are pursuing solutions of including non-medical practitioners e.g., nurse practitioners and physician associates/assistants in their emergency department workforces. This study investigated at the macro and meso level of the health system in England: what the rationale was and the factors influencing the current and future employment, or otherwise, of non-medical practitioners in emergency departments and urgent treatment centres. Methods Mixed qualitative methods in the interpretative tradition were employed. We undertook, in 2021-2022, a documentary analysis of national, regional and subregional policy (2017-2021), followed by semi-structured interviews of a purposive sample (n = 18) of stakeholders from national, regional and subregional levels. The data were thematically analysed and then synthesised. Results There was general national policy support for increasing the presence of non-medical practitioners as part of the solution to shortages of emergency medicine doctors. However, evidence of policy support dissipated at regional and subregional levels. There were no published numbers for non-medical practitioners in emergency departments, but stakeholders suggested they were relatively small in number, unevenly distributed and faced uncertain growth. While the experience of the COVID-19 pandemic and its aftermath were said to have made senior decision makers more receptive to workforce innovation, many factors contributed to the uncertain growth. These factors included: limited evidence on the relative advantage of including non-medical practitioners; variation in the models of service being pursued to address patient demand on emergency departments and the place of non-medical practitioners within them; the lack of a national workforce plan with clear directives; and the variation in training for non-medical practitioner roles, combined with the lack of regulation of that level of practice. Conclusions We identified many features of a system ready to introduce non-medical practitioners in emergency departments and urgent treatment centres but there were uncertainties and the potential for conflict with other professional groups. One area of uncertainty was evidence of relative advantage in including non-medical practitioners in staffing. This requires urgent attention to inform decision making for short- and long-term workforce planning. Further investigation is required to consider whether these findings are generalisable to other specialties, and to similar health systems in other countries.